Analisis Pengaruh Kualitas Manajemen Operasional Terhadap Kinerja Perusahaan - Sri Puspita Sari (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research aims to analyze the influence of operational management quality on company performance. Quality operational management is considered a key factor in creating efficiency, effectiveness and competitiveness. The research results show that there is a significant positive relationship between the quality of operational management and company performance. Aspects such as good planning, process control and continuous improvement contribute greatly to achieving company goals. Additionally, companies that implement good operational management practices demonstrate higher levels of customer satisfaction and reduced operational costs. These findings emphasize the importance of investing in the quality of operational management to improve company performance and competitiveness in an increasingly competitive market. Recommendations for companies include training operational managers, implementing information technology, and emphasizing a culture of continuous improvement.